Co-stimulation With TLR7 Agonist Imiquimod and Inactivated Influenza Virus Particles Promotes Mouse B Cell Activation, Differentiation, and Accelerated Antigen Specific Antibody Production - Li, Can; To, Kelvin K. W.; Zhang, Anna J. X.; Lee, Andrew C. Y.; Zhu, Houshun; Mak, Winger W. N.; Hung, Ivan F. N.; Yuen, Kwok-Yung (Frontiers in Immunology, 2018)
Current influenza vaccines have relatively low effectiveness, especially against antigenically drifted strains, the effectiveness is even lower in the elderly and immunosuppressed individuals. We have previously shown in a randomized clinical trial that the topical application of a toll-like receptor 7 agonist, imiquimod, just before intradermal influenza vaccine could expedite and augment antibody response, including to antigenically-drifted strains. However, the mechanism of this vaccine and imiquimod combination approach is poorly understood. Here, we demonstrated that imiquimod alone directly activated purified mouse peritoneal B cells. When combined with inactivated H1N1/415742Md influenza virus particle (VP) as vaccine, co-stimulation of mouse peritoneal B cells in vitro induced stronger activation, proliferation, and production of virus-antigen specific IgM and IgG. Intraperitoneal injection of a combination of VP and imiquimod (VCI) was associated with an increased number of activated B cells with enhanced expression of CD86 in the mesenteric draining lymph nodes (mesLN) and the spleen at 18 hours after injection. Three days after immunization with VCI, mouse spleen showed significantly more IgM and IgG secreting cells upon in vitro re-stimulation with inactivated virus, mouse sera were detected with viral neutralizing antibody. Transfer of these spleen B cells to naïve mice improved survival after lethal dose of H1N1/415742Md challenge. More importantly, the functional response of VCI-induced B cell activation was demonstrated by early challenge with a lethal dose of H1N1/415742Md influenza virus at 3 days after immunization. The spleen and mediastinal lymph nodes (mdLN) in mice immunized with VCI had germinal centre formation, and significantly higher number of plasmablasts, plasma cells, and virus-antigen specific IgM and IgG secreting cells at only 3-4 days post virus challenge, compared with those of mice that have received imiquimod, inactivated virus alone or PBS. Serum virus-specific IgG2a, IgG2b, and IgG1 and bronchoalveolar lavage fluid (BALF) virus-specific IgA at 3 or 4 days post challenge were significantly higher in mice immunized with VCI, which had significantly reduced lung viral load and 100% survival. These findings suggested that imiquimod accelerates the vaccine-induced antibody production via inducing rapid differentiation of naïve B cells into antigen-specific antibody producing cells.